Thomas Kuhn's Science Paradigm - Fadilah, Ai Aulia; Mulyana, Mulyana; Ramadhan, Ilham Naufal; Harianto, Mahdia Nugraha (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
Thomas Kuhn's thinking in this case is used as an analytical knife to see the revolution in science and education in general. For Thomas Kuhn, the history of science is a starting point in studying fundamental issues in scientific epistemology because science is basically always marked by a strong scientific paradigm and revolution afterward. The purpose of this study is to find out the philosophical foundations of Thomas S. Kuhn's scientific paradigm. The method used is a qualitative approach by applying a descriptive-analytical method. The results of this study show that, according to Kuhn, a paradigm is a set of beliefs, values, methods, and practices that are widely accepted by the scientific community.